The Examination of the Corporate Governance System at Supplier Companies: Empirical Evidence from Hungarian Automotive Industry Ercsey Ida - Ercsey Ida (Journal of Competitiveness, 2016)
Information management and the organizational structure can contribute to the firms’ competitive advantage and business success. In the first part of our study we summarize the results we obtained by analyzing the corporate governance system in connection with the structure of enterprises and their decision making. Then we have an insight into the leadership style of the suppliers from the point of view of the participation of the staff in decision making. In the second part we analyze the information management of the supplier companies on the basis of the answers from the management. We evaluate the strategic and the operational concept of information management, proceeding from the strategy-making activity. The accomplishment of permanent renewal and willingness to innovate are both indispensable for achieving elasticity in organizations. We explore how the suppliers introduce innovation in connection with the firm structure and the information system. Finally, we consider how some essential company characteristics, namely company size, ownership, region, and the width of the product assortment, affect various company functions.